Bearing capacity performance of soft cohesive soil treated by kenaf limited life geotextile - Rashid, A.S.A. (Taylor and Francis Ltd., 2019)
This article presents the performance of the short-term bearing capacity on soft clay soil treated by Kenaf geotextile under vertical loading via a small-scale modelling test at unit gravity. The ground model was formulated by consolidating kaolin in a rigid testing compartment. In the loading test, the strip footing was represented by a rigid footing. For the treated case, a series of tests were performed to examine the effects of the burial depth of the Kenaf geotextile on the bearing capacity of the soft soil. The Kenaf geotextile was laid beneath the rigid footing (at the ground surface) and at 50, 75 and 100 mm depth from the soil surface. All the measured results of the Kenaf geotextile treated ground were compared with the untreated ground. The incorporation of Kenaf fibre geotextile was observed to enhance the bearing capacity of soft cohesive clay up to 281 depending upon the depth of the installed geotextile. The geotextile at the surface provided the highest bearing capacity and sustained the highest displacement at failure. The outcome of this research will promote the use of natural fibre geotextiles as sustainable earth reinforcement in temporary earthwork applications. Â© 2019, Â© 2019 Informa UK Limited, trading as Taylor & Francis Group.